POKEDIS (PODCAST LEADERSHIP IN ISLAM) AS EDUCATION MEDIA ABOUT LEADERSHIP IN ISLAM FOR STUDENTS - Dinda Safitri; Afna Alida; Tias Siti Nurafifah; Ani Nur Aeni (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
Leaders according to Islam are very close to the figure of the Prophet Muhammad SAW who is a role model for Muslims. Leadership in Islam aims to show the way to Allah SWT and achieve His pleasure. As a leader, we must have 4 mandatory characteristics for the Apostle that we can emulate, including Siddiq, Amanah, Tabligh and Fathanah. In addition, a leader who should also have Islamic leadership qualities, namely fair, istiqamah, open and visionary. Many leaders do not imitate the Prophets and Apostles, especially among students. Therefore, the author conducted research on how the product that the author developed could educate students about leadership in Islam. The author's purpose is to find out how to design educational podcast media about Islamic leadership and find out podcast media products for education about Islamic leadership for students. In this study, the author uses a Design and Development (D&D) model research methodology using the ADDIE research procedure (Analyze, Design, Development, Implementation, and Evaluation) where researchers will design, develop and develop a product that has been developed, namely a podcast entitled